Lipid profiling differentiates the effect of ambient microenriched copper on a coral as an advanced tool for biomonitoring. (May 2022) - Tang, Chuan-Ho; Shi, Shu-Han; Lin, Ching-Yu; Wang, Wei-Hsien
Abstract: Copper can be beneficial or harmful to coral at environmentally relevant levels, making environmental monitoring a challenging. Membrane lipids make the cell a dynamic environment according to the circumstances; thus, the lipid profile should be indicative of an environmental/physiological state. To gain more insight into the copper effect on coral health and be a basis of biomonitoring, glycerophosphocholine profiling of coral exposed to microenriched copper levels was conducted in this study. The copper microenrichments resulted in a diacritical effect of decreasing carbonic anhydrase activity, following a supplementation effect, on coral lipid metabolism. Microdifferences in copper levels are critical to determine the coral metabolic state and were therefore included in this study. In addition, an excellent quantitative model correlating the coral lipid variation with the exposed copper levels or the induced physiological effect was obtained to demonstrate its performance for biomonitoring. Highlights: Copper initially exerts a supplementation effect on coral. Moderating transmembrane CO2 flux transforms copper effect on coral. Coral-algal symbiont interaction varies systemic lipid metabolism. Micro-differential copper critically affects the coral lipid metabolism. Coral lipid variations be modeled for environmental biomonitoring.